2014
DOI: 10.1002/jaba.175
|View full text |Cite
|
Sign up to set email alerts
|

A systematic replication of teaching children with autism to respond appropriately to lures from strangers

Abstract: We evaluated the effects of behavioral skills training in the home for teaching children with autism to abstain from going with strangers and immediately inform a familiar adult of the stranger's attempt to lure them in the natural environment. All participants learned to respond correctly to lures in the home and demonstrated concomitant changes in untrained natural settings. In situ training and an added incentive were necessary for 1 participant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 13 publications
3
29
0
2
Order By: Relevance
“…Although several studies have been conducted to evaluate BST, IST, and video modeling for teaching safety skills with typical children (Dancho et al 2008;Gatheridge et al 2004;Himle et al 2004;Johnson et al 2005;Miltenberger et al 2004;Poche et al 1981Poche et al , 1988, little research has been conducted to evaluate these methods with children diagnosed with ASD (e.g., Bergstrom et al 2014;Godish et al 2017;Gunby et al 2010;Gunby and Rapp 2014;Morgan and Miltenberger 2017). Furthermore, this is just the second study to evaluate behavioral procedures for teaching children to avoid pills as a safety threat rather than firearms or abduction lures (Dancho et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been conducted to evaluate BST, IST, and video modeling for teaching safety skills with typical children (Dancho et al 2008;Gatheridge et al 2004;Himle et al 2004;Johnson et al 2005;Miltenberger et al 2004;Poche et al 1981Poche et al , 1988, little research has been conducted to evaluate these methods with children diagnosed with ASD (e.g., Bergstrom et al 2014;Godish et al 2017;Gunby et al 2010;Gunby and Rapp 2014;Morgan and Miltenberger 2017). Furthermore, this is just the second study to evaluate behavioral procedures for teaching children to avoid pills as a safety threat rather than firearms or abduction lures (Dancho et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Observers used the three-point safety rating from previous abduction-prevention research (e.g., Bergstrom et al, 2014) to measure a three-part target response: (a) vocally declining to leave with a stranger, (b) immediately moving away from the stranger, and (c) informing a familiar adult (e.g., therapist) of the incident at first opportunity. Participants could receive a score from 0 to 3 with one point awarded for each step of the response.…”
Section: Data Collection and Interobserver Agreementmentioning
confidence: 99%
“…Gunby and Rapp (2014) extended that work by including a variety of abduction lures (e.g., offering candy, asking child for help). Recently, Bergstrom, Najdowski, and Tarbox (2014) provided a further extension by assessing generalization across environments and abductors. Bergstrom et al (2014) suggested future research should include a variety of lure types in baseline and assess for maintenance of the target response across lures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Türkiye'de ise cinsel istismar vakalarının sıklığı ve dağılımı ile ilgili net bir veri bulunmamakla birlikte istismara uğrayanların sadece %15'inin durumu yetkililere bildirildiği tahmin edilmektedir (Öztop ve Özcan, 2010;Süzer, 2015;Taner ve Gökler, 2004). Tüm bu istatistiklere rağmen ulusal ve uluslararası alanyazında gelişimsel yetersizlik gösteren bireyleri yabancı kişilerden koruma becerilerinin öğretimine ilişkin yayımlanmış araştırma sayısı sınırlı olmakla birlikte, son yıllarda bu konuya ilişkin yayımlanmış çalışmalara daha fazla sayıda rastlamak mümkündür (Akmanoğlu ve Tekin-İftar, 2011;Bergstrom, Najdowski ve Tarbox, 2014;Egemo-Helm ve diğ., 2007;Gunby, Carr ve LeBlanc, 2010;Gunby ve Rapp, 2014;Ledbetter-Cho ve diğ., 2016;Summers ve diğ., 2011).…”
Section: Introductionunclassified